2022
DOI: 10.3390/children9070969
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Macronutrient Intake Determined by Point-of-Care Human Milk Analysis with Brain Development among very Preterm Infants

Abstract: Point-of-care human milk analysis is now feasible in the neonatal intensive care unit (NICU) and allows accurate measurement of macronutrient delivery. Higher macronutrient intakes over this period may promote brain growth and development. In a prospective, observational study of 55 infants born at <32 weeks’ gestation, we used a mid-infrared spectroscopy-based human milk analyzer to measure the macronutrient content in repeated samples of human milk over the NICU hospitalization. We calculated daily nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The benefits of breastfeeding and human milk exposure are well-documented, with studies reporting positive associations between the duration of human milk exposure and total and region-specific brain volumes in infancy and intelligence test scores in early childhood and beyond for those born full-term and preterm [ 11 , 12 , 13 , 14 ]. Although the macronutrient content of human milk has been examined in relation to brain development and neurodevelopmental outcomes [ 15 , 16 ], the composition of human milk is one of the most understudied biological systems in the life sciences. There is also a knowledge gap regarding the mechanisms through which human milk components shape the structural and functional features of the infant brain.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of breastfeeding and human milk exposure are well-documented, with studies reporting positive associations between the duration of human milk exposure and total and region-specific brain volumes in infancy and intelligence test scores in early childhood and beyond for those born full-term and preterm [ 11 , 12 , 13 , 14 ]. Although the macronutrient content of human milk has been examined in relation to brain development and neurodevelopmental outcomes [ 15 , 16 ], the composition of human milk is one of the most understudied biological systems in the life sciences. There is also a knowledge gap regarding the mechanisms through which human milk components shape the structural and functional features of the infant brain.…”
Section: Introductionmentioning
confidence: 99%
“…Early fat and caloric intake have been associated with regional brain volumetrics in preterm infants 12 , 13 , while another study found no relationship 59 . Protein and total energy intake via human milk specifically has also been related to greater total and regional brain volumes 60 . Again, these studies have primarily utilized term equivalent age brain imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we did not prospectively assess nutritional intake, feeding composition, or feeding volumes in the NICU. However, given conflicting evidence, a robust relationship between intake in the NICU and brain growth (as indexed by volumetric analysis of MRI at term equivalent age) is still being established 12 , 13 , 59 , 60 . This could be due to difficulty reliably assessing enteral intake in the NICU, with some investigators finding nutritional intake in their studies failed to meet recommended amounts and others estimating enteral intake based on an assumed composition of maternal breast milk 12 , 13 , 59 , though accurate human milk analysis has been demonstrated to be capably incorporated in these studies 60 .…”
Section: Discussionmentioning
confidence: 99%
“…SWS is a preliminary version of a BE tool available within the Morphologically Adaptive Neonatal Tissue Segmentation (MANTiS) toolbox [42], based on watershed transform. It can be used before the tissue classification pipeline and has been used in several studies [55][56][57][58][59][60][61][62][63][64][65], although it was not used in the validation study of the toolbox (they used BET instead) as it was not available then.…”
Section: Selection Of Automated Brain Extraction Methodsmentioning
confidence: 99%